Integrating Kahoot to Improve Reading Skills through HOTS-Based and Religious Moderation-Oriented Materials - Fudhaili, Achmad; Nurjanah, Neneng; Arifin, Ahmad (Universitas Pendidikan Indonesia (UPI), 2025)
This study designs Arabic reading materials that integrate Higher-Order Thinking Skills (HOTS) with principles of religious moderation to address the cognitive and moral demands of 21st-century education. An integrative pedagogical model employing Kahoot! was implemented to enhance learners’ critical literacy, analytical reasoning, and intercultural awareness. Adopting a descriptive qualitative approach, data were obtained from 15 students through diagnostic assessments and perception surveys. Results revealed promising outcomes, with mean performance scores of 78.6 (range 73–83). Most participants (93.1%) rated the materials as “Highly Suitable” or “Suitable” for developing analytical and evaluative reading skills, while 91.4% agreed they effectively promoted tolerance and inclusivity. Additionally, 62.2% reported heightened motivation and engagement through the gamified environment. The integration of HOTS-oriented questions, multimedia resources, and value-laden texts strengthened both cognitive and affective learning dimensions. However, further enhancement is needed by incorporating synthesis and argumentation tasks and embedding moderation themes in more contextualized narratives. Future development should emphasize adaptive learning, cross-disciplinary integration, and formative feedback to foster autonomy and holistic growth in Arabic language education.